ANALYSIS OF LITERATURE STUDY OF THE EFFECT OF CHICKEN MANURE AND BIO EXTREME BIO-FERTILIZER ON THE GROWTH OF LAND KANGKUN (Ipomoea Reptans Poir): ANALISIS STUDI LITERATUR PENGARUH PUPUK KANDANG AYAM DAN PUPUK HAYATI BIO EXTRIM TERHADAP PERTUMBUHAN TANAMAN KANGKUN DARAT (Ipomoea Reptans Poir) - Gulo, Primuadin (UPMI Proceeding Series, 2024)
Vegetable plants are needed by humans to meet the nutritional and mineral intake in the body. Water spinach is a horticultural plant that is popular with the Indonesian people, in addition to its savory taste, water spinach contains many benefits. This study aims to analyze and summarize the results of literature studies on the effect of chicken manure and bio-extreme organic fertilizer on the growth and production of land spinach (ipomeae reptans poir). Chicken manure contains various types of nutrients that are very beneficial for plants, including Nitrogen, Phosphorus and Magnesium. Meanwhile, Biofertilizer is a biological product that can increase fertilization efficiency, fertility and soil health. Based on a literature review, the combination of chicken manure and bio-extreme organic fertilizer shows significant results in increasing the growth and production of land spinach. Several studies have shown that the balanced use of chicken manure and bio-extreme organic fertilizer can improve nutrient absorption by plants and increase resistance to pest and disease attacks. However, the effectiveness of this application is highly dependent on the dose used, soil conditions, and environmental factors. This study also identified differences in results due to variations in application methods and types of varieties used. Overall, these findings suggest the need for further research to optimize the right combination of fertilizers to increase sustainable land spinach production.